2020
DOI: 10.1177/0748233720964650
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of airborne SARS-CoV-2 infection transmission risk in New York City nail salons

Abstract: Although airborne transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from person-to-person over long distances is currently thought to be unlikely, the current epidemiological evidence suggests that airborne SARS-CoV-2 infection transmission in confined, indoor spaces is plausible, particularly when outdoor airflow rates are low and when face masks are not utilized. We sought to model airborne infection transmission risk assuming five realistic exposure scenarios using previously esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 32 publications
2
49
0
1
Order By: Relevance
“…Previous investigators have concluded that carbon dioxide (CO 2 ) concentrations, when used as a proxy for ventilation rates, can indicate the potential presence of airborne SARS-CoV-2 27 and, subsequently, the risk of aerosol transmission in confined, indoor spaces. 28 The objective of this study was to estimate the risk of SARS-CoV-2 transmission among New York City public school students and teachers under steady-state conditions using previously collected classroom CO 2 concentrations. While three modes of transmission (1. contact via fomites, 2.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators have concluded that carbon dioxide (CO 2 ) concentrations, when used as a proxy for ventilation rates, can indicate the potential presence of airborne SARS-CoV-2 27 and, subsequently, the risk of aerosol transmission in confined, indoor spaces. 28 The objective of this study was to estimate the risk of SARS-CoV-2 transmission among New York City public school students and teachers under steady-state conditions using previously collected classroom CO 2 concentrations. While three modes of transmission (1. contact via fomites, 2.…”
Section: Introductionmentioning
confidence: 99%
“…A deliberate consideration on these superspreading phenomena, would rather prefer aerosol-mediated transmission 15 to conventional contact or large droplet-mediated ones 16 . A mathematical estimation that only 10-20% were supposed to transmit to 80% of the whole patients 17 , would further support the accountability of aerosol infection for lots of large cluster infections.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of studies during the pandemic support the key role of social distancing in reducing transmission, particularly in crowded communities and households 4 . The arguments in favour of physical distancing are based on the concept that virus is spread by exhaled breath in both droplet and aerosol form and may remain airborne for variable periods of time depending on the atmospheric conditions, propulsion of air, available ventilation and the viral load in exhaled breath 5,6 . In a systematic review of 172 observational studies, transmission of viruses was lower with physical distancing of 1 m or more, compared with a distance of less than 1 m (adjusted odds ratio (OR): 0.18, 95% CI: 0.09–0.38) and protection was increased as distance was lengthened (change in relative risk (RR): 2.02 per m) 7 .…”
mentioning
confidence: 99%
“…4 The arguments in favour of physical distancing are based on the concept that virus is spread by exhaled breath in both droplet and aerosol form and may remain airborne for variable periods of time depending on the atmospheric conditions, propulsion of air, available ventilation and the viral load in exhaled breath. 5,6 In a systematic review of 172 observational studies, transmission of viruses was lower with physical distancing of 1 m or more, compared with a distance of less than 1 m (adjusted odds ratio (OR): 0.18, 95% CI: 0.09-0.38) and protection was increased as distance was lengthened (change in relative risk (RR): 2.02 per m). 7 In a Swiss study, social distancing slowed the spread of SARS-CoV-2 in a cohort of young, healthy adults which still induced an immune response and colonized nasal passages.…”
mentioning
confidence: 99%
See 1 more Smart Citation